Feasibility to Measure Tissue Oxygen Saturation Using Textile-Integrated Polymer Optical Fibers - Cantieni, Tarcisi; da Silva-Kress, O; González, M; Michler, M; Rastija, T; Grabher, R; Piai, G; Ansari, N; Sharma, K; Morlec, E; Camenzind, M; Boesel, L; et al. (Advances in experimental medicine and biology, 2022)
Tissue oxygen saturation (StO ) is a crucial factor in the aetiology of pressure injury (PI), since hypoxia leads to necrotization. Pressure on the tissue occludes blood circulation and reduces the StO , resulting in hypoxia. PI causes severe suffering, heals slowly and is expensive to treat. Hence it is important to prevent PI by detecting hypoxia, e.g., by near-infrared spectroscopy (NIRS) monitoring of StO . For this, the NIRS device has to be wearable for a long time and it is crucial that it provokes no pressure itself. An integration of optical fibres into a textile achieves this. The aim was to investigate the feasibility of such a textile NIRS device.Knots and loops were tested as textile light emitters (LEs) or detectors (LDs) on a phantom. The light coupling efficiency of the LEs and LDs was investigated.Results show that knots perform similarly to loops. More loops per fibre increase efficiency both in LEs and in LDs. The best trade-off is at 3 loops. LEs are slightly more efficient than LDs, with an average attenuation from baseline of about -2 dB for loops of 0.5 mm diameter. Adding fibres multiplies the signal by the number of fibres. Inclusions mimicking hypoxia in phantoms were successfully identified. In-vivo arm occlusion tests showed the expected decrease in StO . This shows feasibility of optical fibres in a textile to prevent PI.